Schönheitsdiskurse in der Literatur des Mittelalters Die Propädeutik des Fleisches zwischen ,aisthesis' und Ästhetik - Scheidel, Fabian David (Literatur - Theorie - Geschichte, 2022)
This study provides a fundamental new reading of numerous commonplace positions in Germanic medieval studies relating to the physical beauty of literary figures. It looks at both canonic and more marginal Middle High German poems ("Erec," "Parzival," "Welscher Gast" [The Romance Stranger]) as well as their Medieval Latin context (poetorhetorics) and their discursive matrix, which is based in theology.